PERMASALAHAN KERJASAMA UNI EROPA DALAM MENGHADAPI ISU PENCARI SUAKA - Ari Ramadhan (HI 16 UMY 149, 2016)
*149 Known by successful regional cooperation system in various issues, The European Union serve as a role model for many regional organizations in the world. However, nowadays European Union is facing the migration of asylum seekers that causes various problems and makes solidarity in EU disrupted. This is shown by member countries of European Union that still can't unify their voices together in dealing with the issue. This article will explain the problems that occur within European Union while resolving this issue. To address the problem, the analisys of this article based on intergovernmentalism in regional organization. The European Union's solidarity is being tested in dealing with migration of asylum seekers issue.